2002
DOI: 10.1016/s1350-4177(02)00083-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ultrasonic cavitation yield by multi-frequency sonication

Abstract: The paper reports the enhanced effect of multi-frequency ultrasonic irradiation on cavitation yield. The cavitation yield is characterized by electrical conductivity determination, fluorescence intensity determination and iodine release method. Two-frequency (28 kHz/0.87 MHz) orthogonal continuous ultrasound, two-frequency (28 kHz/0.87 MHz) orthogonal pulse ultrasound and three-frequency (28 kHz/1.0 MHz/1.87 MHz) orthogonal continuous ultrasound have been used. It has been found that the combined irradiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(127 citation statements)
references
References 8 publications
4
122
0
1
Order By: Relevance
“…Practical importance especially in medicine of a high-frequency force has been reported [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Practical importance especially in medicine of a high-frequency force has been reported [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The CD spectra of zein (0.2 mg/mL in 60% ethanol) were assessed at a wavelength range of 190-250 nm with a Jasco J-715 CD spectropolarimeter (Jasco Corp., Tokyo, Japan) using a quartz cuvette with a 10-mm optical path length under nitrogen flux at a temperature of 25 ∘ C, scanning rate of 50 nm/min, and bandwidth of 1.0 nm. The content of the protein secondary structure was calculated from the far-UV CD spectra using the DICHROWEB procedure [18][19][20][21][22].…”
Section: Circular Dichroism (Cd)mentioning
confidence: 99%
“…A comparison of two studies, Entezari and Kruus (1996) performed at 20 and 900 kHz and Seymour et al (1997) at 640 kHz, showed a higher cavitation yield at sonication frequency of 640 kHz compared to 20 and 900 kHz. Furthermore, a study by Feng et al (2002) reported that when using the low MHz frequency range, the lower the frequency used, the higher the cavitation yield. They observed that the sound intensity of low MHz frequency ultrasound is above 6 W cm -2 , and the cavitation yield of the combined irradiation (0.87 MHz and 28 kHz) is more than 1.6 times of that of combined irradiation using a higher MHz frequency (1.7 MHz and 28 kHz).…”
Section: Effect Of Sonication Frequencymentioning
confidence: 99%